2009
DOI: 10.1536/ihj.50.59
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Heart Rate Profiles During Cardiopulmonary Exercise Testing in Patients With Cardiac Disease

Abstract: SummaryEarlier studies have demonstrated that an impaired capacity to increase heart rate (HR) and a slowed HR recovery following exercise are both associated with cardiovascular mortality. We sought to determine whether HR profiles during exercise testing are superior to respiratory gas parameters in predicting mortality among patients with cardiac disease.Five-hundred and fifty stable cardiac patients (63.4 ± 9.9 years) underwent a symptom-limited incremental exercise test. Measurements included peak VO2, VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Most of these patients (90%) were treated with betablockers, and results are consistent with previously cited works. Similar to the present findings Goda et al [31] reported, using HR increase (HR difference from rest to peak exercise) and HRR (HR difference from peak to 2 min after exercise) as HR parameters and CEPT parameters, that although HR profiles during exercise are easy to perform and useful prognostic markers in patients with cardiovascular disease (ischemic heart disease, valvular heart disease, cardiomyopathies), they are not superior to respiratory gas analysis [31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Most of these patients (90%) were treated with betablockers, and results are consistent with previously cited works. Similar to the present findings Goda et al [31] reported, using HR increase (HR difference from rest to peak exercise) and HRR (HR difference from peak to 2 min after exercise) as HR parameters and CEPT parameters, that although HR profiles during exercise are easy to perform and useful prognostic markers in patients with cardiovascular disease (ischemic heart disease, valvular heart disease, cardiomyopathies), they are not superior to respiratory gas analysis [31].…”
Section: Discussionsupporting
confidence: 89%
“…The results need to be confirmed in larger, multicenter studies. A small group of the presented patients had atrial fibrillation, as in other previous studies [7,26,31], so generalizing results to patients with atrial fibrillation must be done with caution. This group of patients needs further study.…”
Section: Limitations Of the Studymentioning
confidence: 77%
“…However, elevated heart rate is not commonly used as an indicator of heart damage. Rather, inability for a patient's heart to increase its rate in response to physical stress is an indicator of damage postinfarct [42,43,44,45]. However, it is thought that faster pulse is induced as a compensatory measure as animals attempt to maintain sufficient outflow [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The most common CVDs were coronary artery disease 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 and heart failure, 33 , 34 , 35 , 36 , 37 and other studies included patients diagnosed with aortic stenosis, 22 hypertrophic cardiomyopathy, 38 peripheral artery disease, 39 and a combination of various pathologies. 21 , 40 , 41 , 42 General characteristics of the 21 included studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“… Study Follow-up (month) Sample size (women/men) Mean age (year) Disease condition Exposure measurement Outcome High vs . low definition Per increment definition Number of deaths Adjustment for covariates Aijaz et al (2009) 26 120.0 282 (48/234) 61.0 Coronary heart disease Cardiopulmonary treadmill testing (symptom-limited graded exercise testing) All-cause mortality Low: VO 2peak <19 mL/kg/min (men) and <15 mL/kg/min (women) 55 Age and gender Barons et al (2015) 27 136.0 2714 (547/2167) 61.3 Coronary heart disease Exercise test using the Bruce protocol or the modified Bruce protocol All-cause mortality and CVD mortality VO 2peak ≥ 22 mL/kg/min (men), VO 2peak ≥ 19 mL/kg/min (women, high) vs. VO 2peak <15 mL/kg/min (women, low) 385 (all-cause) and 192 (CVD) NR Coats et al (2015) 38 67.2 1898 (626/1272) 46.0 Hypertrophic cardiomyopathy Maximal exercise test All-cause mortality, or CVD mortality, sudden cardiac death, and heart failure death Per 1 mL/kg/min increase in VO 2peak 156 (all cause) and 117 (CVD) Age, sex, and all exercise parameters Dhoble et al (2014) 22 61.2 155 (16/139) 69.6 Aortic stenosis Maximal exercise test All-cause mortality VO 2peak ≥ 19 mL/kg/min (men) or ≥ 15 mL/kg/min (women), or ≥ 80% (high) vs. <80% (low) for men and women 41 Age, gender, symptom status, Charlson index, and AV area Goda et al (2009) 40 45.6 549 (112/437) 63.4 Various (ischemic heart disease, valvular heart disease, dilated cardiomyopathy, hypertr...…”
Section: Resultsmentioning
confidence: 99%